DETERMINING THE BOILING DOWN OF SNAIL MEAT - Danilova, I. S.; Danilova, T. N. (Scientific Progress & Innovations, 2019)
The increase of food production is one of the main problems facing the agro-industrial complex of Ukraine in modern conditions. It is possible that in the near future a new business will appear in Ukraine connected with the production of snails on the industrial basis. Thus, determining the weight loss of food snail meat is the important issue. The studies were carried out on snails of Helix pomatia, Helix aspersa maxima and Helix aspersa muller species. The selected samples of meat were cooked for different periods of time from the moment of boiling. At the end of cooking, the difference between raw meat and boiled meat was considered to be the meat loss. Before cooking, all meat samples were weighed. The reliability of the obtained data was calculated using the “Sadovsky” computer program by determining the arithmetic mean (M) and its error (m) and analyzed only between them, because such information is not available. The following dependence was established: the smaller the sample of meat was, the greater was the loss, and the more time it took to boil the meat, the percentage of meat loss was also greater. The meat of all the three experimental snail species began to lose weight in 30 minutes and the percentage of loss ranged from 34.37 % to 37.66 %. It was found that the percentage of Helix pomatia snail meat loss was 38.93 % on the average, while Helix aspersa muller snail meat was 40.86% and Helix aspersa maxima was 42.78 %. Significant fluctuations of the meat weight loss during boiling were detected for all the investigated types of snails. We established that after 90 minutes of boiling snail meat taken for the experiment, as compared with the boiling time of 30 and 60 minutes, the data concerning the percentage of loss differed. Thus, the lowest percentage of loss in ready-to-eat snail meat was in Helix pomatia – 38.93 %, and the largest – 42.78 % was observed in Helix aspersa maxima. According to our data it can be maintained that the percentage of meat loss of the experimental snail species as compared with the raw meat varies within the following limits: in 30 minutes (in %) by 37.66:34.37:37.51 correspondingly; in 60 minutes (in %) by 38.06:39.71:39.24, respectively, and for 90 minutes (in %) at 38.93:42.78:40.86, correspondingly.